2013
DOI: 10.3928/01477447-20130624-13
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Neck Shortening After Internal Fixation of a Femoral Neck Fracture

Abstract: This study assesses femoral neck shortening and its effect on gait pattern and muscle strength in patients with femoral neck fractures treated with internal fixation. Seventy-six patients from a multicenter randomized controlled trial participated. Patient characteristics and Short Form 12 and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores were collected. Femoral neck shortening, gait parameters, and maximum isometric forces of the hip muscles were measured and differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 24 publications
3
95
4
1
Order By: Relevance
“…Femoral neck shortening and varus displacement of the femoral head following internal fixation of femoral neck fractures are commonly found in a clinical setting. Neck shortening has been shown to negatively affect the clinical outcome in healed fractures (Zlowodzki et al 2008, Zielinski et al 2013. Although our study revealed that interlocking of the three screws significantly reduced the deformation of the proximal femur, the new implant was not able to resist the unwanted femoral neck shortening and varus displacement of the femoral head.…”
Section: Study Icontrasting
confidence: 42%
“…Femoral neck shortening and varus displacement of the femoral head following internal fixation of femoral neck fractures are commonly found in a clinical setting. Neck shortening has been shown to negatively affect the clinical outcome in healed fractures (Zlowodzki et al 2008, Zielinski et al 2013. Although our study revealed that interlocking of the three screws significantly reduced the deformation of the proximal femur, the new implant was not able to resist the unwanted femoral neck shortening and varus displacement of the femoral head.…”
Section: Study Icontrasting
confidence: 42%
“…Also shortening of limb length and limitations in limb range of motion are more common after fixation than after arthroplasty (Parker et al 2002). Femoral neck shortening after internal fixation induces walking asymmetry, decreased walking velocity and impaired physical functioning, leading to permanent physical limitations (Zielinski et al 2013). The results of a recent randomized controlled trial suggested that physical functioning, activities of daily living and quality of life favored hemiarthroplasty compared to internal fixation in the first two years, but statistically significant differences between the two surgical methods were no longer found six years after the hip fracture (Stoen et al 2014).…”
Section: Risk Factors For Hip Fracture 212mentioning
confidence: 99%
“…A recent multicenter study using a questionnaire demonstrated that patients with severe shortening of the femoral neck accompanied a significant reduction in hip abductor strength and postoperative function. 13 In another study of patients undergoing rehabilitation, diminished strength of multiple lower extremity muscles, including hip extensors and abductors, was shown to have a deleterious effect on gait speed and on maintaining upright balance during the stance phase of walking. 16 These two articles clearly demonstrate functional deterioration among postoperative patients with weakened muscles.…”
Section: Muscular Strength and Function Decreases Secondary To Femoramentioning
confidence: 99%